KUAT LENTUR PANEL DINDING BETON BUSA DENGAN LAPIS GRC DAN WIREMESH - Lilis Tiyani; Iman Satyarno; Ashar Saputra (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2019)
Lightweight concrete is high in demand as it offers lighter specific gravity which makes the load on the structure smaller. In this research, lightweight concrete was produced by mixing water, cement, sand and foam. Besides aiming to obtain lighter specific gravity, the target of this research was also to design lightweight foam concrete with compressive strength equal to the one of commonly used materials for walls of around 3-5 MPa. However, foam concrete has relatively weaker tensile strength, that it would be inadequate when it has to hold the vertical force of the wall when it is applied as wall panels. This research was conducted to examine the flexural strength of the use of GRC coating and wiremesh for wall panels. Cylinder test was performed using tools with a size of 150 mm in diameter x 300 mm in length to analyze the modulus of elasticity at 28 days old, and three cubical test tools for each variance with a size of 50 mm x 50 mm x 50 were employed to test the tensile strength at 28 days old. A number of wall panel specimens with a thickness of 50 mm, width of 400 mm and length of 800 mm were used to measure the flexural strength. The tests performed in this research resulted in modulus of elasticity of 6856,6 MPa, tensile strength of 0,7 MPa. The flexural strength of wall panels without GRC outer layer and without wiremesh reinforcement was found at 1,5 MPa. Meanwhile, the flexural strength of the wall panel with GRC outer layer without wiremesh reinforcement was found at 4,6 MPa. Finally, the wall panel applied with GRC outer layer and wiremesh reinforcement showed a flexural strength 5,3 MPa.